2018
DOI: 10.1029/2017wr022216
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns of Water Age: Using Young Water Fractions to Improve the Characterization of Transit Times in Contrasting Catchments

Abstract: Transit time distributions (TTDs) are crucial descriptors of flow and transport processes in catchments, which can be determined from stable water isotope data. Recently, the young water fraction (F yw ) has been introduced as an additional metric derivable from seasonal isotope cycles. In this study, we calculated F yw and TTDs using monthly isotope data from 24 contrasting subcatchments in a mesoscale catchment (3,300 km 2 ) in Germany. F yw ranged from 0.01 to 0.27 (mean = 0.11) and was smallest in mountain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
129
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(140 citation statements)
references
References 68 publications
(146 reference statements)
11
129
0
Order By: Relevance
“…4b), raising the question of whether a curve fit with R 2 adj = 0.6 is objectively better than a fit with R 2 adj = 0.3 when the underlying isotope data have completely different amplitudes. A decrease in the goodness of fit of the sine wave when amplitudes are low was also found by Lutz et al (2018).…”
Section: Fraction Of Young Watermentioning
confidence: 59%
See 4 more Smart Citations
“…4b), raising the question of whether a curve fit with R 2 adj = 0.6 is objectively better than a fit with R 2 adj = 0.3 when the underlying isotope data have completely different amplitudes. A decrease in the goodness of fit of the sine wave when amplitudes are low was also found by Lutz et al (2018).…”
Section: Fraction Of Young Watermentioning
confidence: 59%
“…The variability in Fyw(189) of this study could not be explained by meteorological or hydrometric variables. Lutz et al (2018) found a negative correlation between annual precipitation and Fyw. The study of 22 Swiss catchments by von Freyberg et al (2018) found significant positive correlations between Fyw and mean monthly discharge and precipitation volumes.…”
Section: Hypothesis 1 -Fyw Is Time-variantmentioning
confidence: 91%
See 3 more Smart Citations